MUSLIM-BASED PARTIES AND THE STRATEGIC USE OF POLARIZATION IN INDONESIA’S MULTIPARTY POLITICS AFTER 2014 - Herdiansah, Ari Ganjar; Sumadinata, Raden Widya Setiabudi; Pratisti, Aliyuna (JWP (Jurnal Wacana Politik), 2026)
The article explores how Indonesian Muslim-based parties are structurally responding to, and using, post-2014 polarization in coalition politics through party institutionalization. Party institutionalization is understood as the mediator that shapes how polarization results in coalition formation, internal organizational dynamics, and electoral performance. A comparative case study of PKB, PKS, PAN, and PPP is covered here, based on interviews with party elites and activists for Islamic organizations, along with secondary sources, electoral reports, and media coverage. Results indicate patterned variation across parties. PKB and PKS, with more cohesive constituencies and stronger organizational capacity, have been able to better exploit the impact of polarization to reinforce partisan identity and enhance electoral prospects: PKB with an entrenched relationship with the Nahdlatul Ulama (NU) milieu, while PKS uses polarization to consolidate after earlier internal frictions and expand its appeal among conservative electorates. In contrast, PAN’s more heterogeneous base creates tensions between the elite when a coalition’s maneuvers alienate an aspect of its supporters, whereas PPP’s weak organizational solidity propels it towards government alignment despite misfit with its base of voters. Overall, depending upon party institutionalization, polarization becomes either an electoral resource or an organizational burden.